Obesity and Gut Microbiota: what do we know so far? - Machuga de Almeida, Laura; Zimberg Chehter, Ethel (Seven Editora, 2023)
Introduction: Obesity is a matter of global concern, which has been rising over the last decades. It is estimated that more than 600 million adults are obese. Treatments, such as changes in lifestyle, medications (Liraglutide) and bariatric surgery are well established in literature. The role of the gut microbiome in obesity involves many pathways, as in the glucose and leptin homeostasis, increasing in activity of enteroendocrine cells and maintenance of GLP-2. The impact of the microbiota in reduction of BMI, abdominal circumference and body fat. The main objective of this paper is to find the data known until this moment about the role of gut microbiota in obesity and the gaps in this relation. Method: search in literature using the PRISMA method for articles about gut microbiome and obesity, trying to find the gaps in this relation. Result: studies have shown associations between microbiota’s species and obesity in diverse populations. It has been observed that probiotic’s supplementation associated with diet had more impact on weight and body fat than diet only. Probiotics also impact in DM1 and DM2, metabolic syndrome and pregnancy. Discussion: More systematized studies are necessary to understand which species and quantities lead to clinical results, in order to apply the practical use of these supplements. Conclusion: Although more studies are necessary to elucidate the practical supplementation, the influence of gut microbiota in obesity is already clear. DOI: https://doi.org/10.56238/tfisdwv1-037